Sub Sinus Ridge Height at First Molar Region- A Panoramic Radiograph Based Study - Pandey, Nashib; Gupta, Sujaya; Shah, Ankit; Khapung, Anju; Dhami, Bhageshwar (Journal of Nepal Health Research Council, 2020)
Background: Among various replacement options available for maxillary molars, implants necessitate the need to examine available ridge height and width. Panoramic radiographs (orthopantomograms) are routinely used for preliminary determination of ridge height which is helpful in communicating with patients regarding treatment needs and options. This study was designed with the aim to assess the sub sinus ridge height at dentulous and edentulous first molar sites.Methods: A cross-sectional study was conducted from March to November 2019 among patients visiting the dental college. The orthopantomograms of 455 patients were prospectively collected and analysed using Carestream imaging software (version 7.0.0). Distance from alveolar crest to maxillary sinus was measured in first molar region. Results: Mean minimal sub sinus ridge height at non-missing maxillary first molar site was 8.16 ± 2.6 mm, whereas for missing maxillary first molar site it was 5.25 ± 2.28 mm and the difference was statistically significant (p<0.001). Statistically significant difference among the age groups and minimum subsinus ridge height (p<0.001) was observed. Conclusions: Missing maxillary first molar sites may often require vertical bone augmentation with direct sinus lifting procedures if it has to undergo replacement with dental implants in the representative Nepalese population.Keywords: Implant; Nepalese; orthopantomogram; panoramic radiography; sinus augmentation